The activation of P1- and P2-purinoceptors in the guinea-pig left atrium by diadenosine polyphosphates. - Hoyle, C. H. (1996)
1. The effects of P1, P2-di(adenosine) pyrophosphate (AP2A), P1, P3-di(adenosine) triphosphate (AP3A), P1,P4-di(adenosine) tetraphosphate (AP4A), P1,P5-di(adenosine) pentaphosphate (AP5A), ATP, alpha, beta-methylene ADP and 2-chloroadenosine (2-ClAd) were examined in the guinea-pig driven left atrium. 2. All these purine compounds except alpha, beta-methylene ADP produced a negative inotropic response with a rank order of potency of: 2-ClAd > > AP2A > or = ATP > or = AP4A = AP3A = AP5A. The EC50 value for 2-ClAd was approximately 1 microM, while those for the remaining compounds were in the range 10 microM-100 microM, alpha, beta-Methylene ADP (10-300 microM), a selective P2Y-purinoceptor agonist, produced a small positive inotropism. 3. The P1-purinoceptor antagonist, 8-para-sulphophenyltheophylline (8-pSPT, 20 microM) caused a right-ward shift in the concentration-response curves for 2-ClAd, ATP and AP2A, but converted the responses of AP3A, AP4A, and AP5A into positive inotropisms. 4. The non-selective P2-purinoceptor antagonist, suramin (300 microM), had no significant effect on the concentration-response curves for 2-ClAd, ATP or AP2A, but significantly antagonized inhibitory responses to AP3A, AP4A and AP5A, and excitatory responses to alpha, beta-methylene ADP. 5. In the presence of 8-pSPT (20 microM), suramin (300 microM) abolished the positive inotropic responses evoked by the dinucleotides. 6. ATP was degraded far more rapidly than any of the dinucleotides, and AP3A was the least stable of the diadenosine compounds. The relative order of stability was AP2A > AP4A = AP5A > AP3A > > ATP. Suramin (300 microM) reduced the rate of degradation of ATP and AP3A by approximately 30%. Suramin had no significant effect on the degradation of AP2A, AP4A or AP5A. 7. It is concluded that the diadenosine polyphosphates cause negative inotropic responses via P1-purinoceptors and a hitherto undefined suramin-sensitive P2-purinoceptor, and that they appear to have positive inotropic effects mediated via another suramin-sensitive P2-purinoceptor.